2019
DOI: 10.1371/journal.pone.0221641
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DNA methylation during epigenetic-associated sex reversal under low temperature in Takifugu rubripes

Abstract: DNA methylation has frequently been implicated in sex determination and differentiation in teleost species. In order to detect the DNA methylation patterns established during sexual differentiation in tiger pufferfish T . rubripes , we performed comprehensive whole genome methylation sequencing and analyses of the gonads of male, female, and pseudo male. We obtained a total of 33.12, 32.44, and 31.60 Gb clean data for male, female, and pseudo male, with a sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Our analysis on the haploid and diploid methylome profiles of tiger pufferfish found that about 10.80% of C was methylated in both genetic female and male genomes, which is consistent with our previous reports in adult tiger pufferfish [26] and Chinese tongue sole (Cynoglossus semilaevis) [27]. The global DNA methylation level in haploid fish was higher than that in diploid females and males.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis on the haploid and diploid methylome profiles of tiger pufferfish found that about 10.80% of C was methylated in both genetic female and male genomes, which is consistent with our previous reports in adult tiger pufferfish [26] and Chinese tongue sole (Cynoglossus semilaevis) [27]. The global DNA methylation level in haploid fish was higher than that in diploid females and males.…”
Section: Discussionsupporting
confidence: 91%
“…High mC in the CG context is also observed in other vertebrate genomes such as Chinese tongue sole (Cynoglossus semilaevis) (Shao et al, 2014), tiger pufferfish (Takifugu rubripes) (Zhou et al, 2019), human (Lister et al, 2009) and chicken (Li et al, 2011), suggesting that DNA methylation in the nucleus mainly exists in CG sites in vertebrates. Approximate 9% of C in Chinese tongue sole and 11% of C in tiger pufferfish are methylated in their gonadal genomes.…”
Section: Discussionmentioning
confidence: 86%
“…For example, methylation may abrogate the stimulation of cyp19a1a by gonadotropins in a male-specific fashion in ricefield eel (Zhang et al, 2013). Zhou et al (2019) also found whole genome methylation difference for sex changes under low temperature in Takifugu rubripes. Above all, sex-determination system in fish is complicated and needs different level of data to uncover the key modules which played key roles in it (Ortega-Recalde et al, 2020).…”
Section: Introductionmentioning
confidence: 81%